G-CSF-induced sympathetic tone provokes fever and primes antimobilizing functions of neutrophils via PGE2 - Kawano, Yuko; Fukui, Chie; Shinohara, Masakazu; Wakahashi, Kanako; Ishii, Shinichi; Suzuki, Tomohide; Sato, Mari; Asada, Noboru; Kawano, Hiroki; Minagawa, Kentaro; Sada, Akiko; Furuyashiki, Tomoyuki; et al. (Blood, 2017)
Granulocyte colony-stimulating factor (G-CSF) is widely used for peripheral blood stem/progenitor mobilization. G-CSF causes low-grade fever that is ameliorated by nonsteroidal anti-inflammatory drugs (NSAIDs), suggesting the activation of arachidonic acid (AA) cascade. How G-CSF regulated this reaction was assessed. G-CSF treatment in mice resulted in fever, which was canceled in prostaglandin E synthase (mPGES-1)-deficient mice. Mobilization efficiency was twice as high in chimeric mice lacking mPGES-1, specifically in hematopoietic cells, suggesting that prostaglandin E2 (PGE2) from hematopoietic cells modulated the bone marrow (BM) microenvironment. Neutrophils from steady-state BM constitutively expressed mPGES-1 and significantly enhanced PGE2 production in vitro by β-adrenergic stimulation, but not by G-CSF, which was inhibited by an NSAID. Although neutrophils expressed all β-adrenergic receptors, only β3-agonist induced this phenomenon. Liquid chromatography–tandem mass spectrometry traced β-agonist-induced PGE2 synthesis from exogenous deuterium-labeled AA. Spontaneous PGE2 production was highly efficient in Gr-1high neutrophils among BM cells from G-CSF-treated mice. In addition to these in vitro data, the in vivo depletion of Gr-1high neutrophils disrupted G-CSF-induced fever. Furthermore, sympathetic denervation eliminated both neutrophil priming for PGE2 production and fever during G-CSF treatment. Thus, sympathetic tone-primed BM neutrophils were identified as one of the major PGE2 producers. PGE2 upregulated osteopontin, specifically in preosteoblasts, to retain progenitors in the BM via EP4 receptor. Thus, the sympathetic nervous system regulated neutrophils as an indispensable PGE2 source to modulate BM microenvironment and body temperature. This study provided a novel mechanistic insight into the communication of the nervous system, BM niche components, and hematopoietic cells. •G-CSF-induced sympathetic tone provokes fever and modulates microenvironment via PGE2 production by bone marrow Gr-1high neutrophils.